8
$\begingroup$

Could anyone help me to do this integral ?

$$\int_{\,0}^\infty \; \frac{\exp \left( -\frac{1}{x} -x\right)}{\sqrt{x}} \, dx = \sqrt{\pi}e^{-2} $$

I think you start with completing the square in the exponent, but what substitution do you make then ? $u=\sqrt{x}$ didn't seem to get me far.

$\endgroup$
  • $\begingroup$ Are you familiar with Error Functions? $\endgroup$ – Inquest Oct 15 '12 at 18:17
  • $\begingroup$ Does $\displaystyle \frac{1}{\sqrt x}= \frac{2}{\sqrt{\pi}} \int_{0}^{\infty} e^{-xt^2} dt$ help? Anyway, (+1) for the question. $\endgroup$ – user 1357113 Oct 15 '12 at 18:18
  • 1
    $\begingroup$ @JoeKing: This is a special case of the integral dealt with here. This is the case $n = t = 1/\sqrt{\pi}$. $\endgroup$ – user26872 Oct 15 '12 at 20:17
10
$\begingroup$

Substitute first $x=u^2$ in order to have:

$$ I = \int_{0}^{+\infty}\frac{dx}{\sqrt{x}\exp\left(x+\frac{1}{x}\right)}=2\int_{0}^{+\infty}e^{-\left(x^2+\frac{1}{x^2}\right)}\,dx$$

Use now the substitution $x=\frac{1}{y}$ to have:

$$ I = 2\int_{0}^{+\infty}\frac{1}{x^2}e^{-\left(x^2+\frac{1}{x^2}\right)}\,dx,$$

from which follows:

$$ I = \int_{0}^{+\infty}\left(1+\frac{1}{x^2}\right)e^{-\left(x^2+\frac{1}{x^2}\right)}\,dx,$$

and the key substitution is now $u = x-\frac{1}{x}$, from which we have:

$$ I = \int_{-\infty}^{+\infty}e^{-u^2-2}\,du = e^{-2}\sqrt{\pi}, $$

QED.

$\endgroup$
  • $\begingroup$ Nice and simple (+1). $\endgroup$ – user 1357113 Oct 15 '12 at 18:30
  • $\begingroup$ Wow. I would never have worked that out. Was it obvious to you ? $\endgroup$ – Joe King Oct 15 '12 at 18:45

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.